STEM-based mathematics learning module with PBL model in improving higher-order thinking skills - Ayunda Nova Millania; Agus Prasetyo Kurniawan; Ahmad Lubab; Ahmad Choirul Anam (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
The development of STEM-based mathematics learning modules that are systematically arranged using the PBL (Problem-Based Learning) model is one way to train students' higher-order thinking skills (HOTS). This study aims to describe the process, validity, and practicality of the developed mathematics learning module and determine the students' higher-order thinking skills after using the mathematics learning module using the development research type. This STEM-based mathematics learning module with the PBL model was developed referring to the ADDIE development model, which consists of 5 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The math learning module focuses on statistical material on the size of data concentration given to class VIII students at UPT SMPN 9 Gresik, as many as 31 students. Implementation begins with analyzing the results of instrument validation by validators, then analyzing student response questionnaires filled out by students after using the learning module and through higher-order thinking skills tests. Based on the results of the development process, it can be concluded that students still have difficulty working on higher-order thinking skills at the initial stage, namely the analysis stage. Designing and making modules are carried out at the design stage and development stages. At the implementation stage, the module was tested and declared feasible by the validator. The last stage is the evaluation stage, namely analyzing the data that has been obtained. The results of the validation of this math learning module are in the very valid category, with an average total validity (RTV) value of 4.16 by the three validators. The math learning module was also declared practical in theory with an average score of B, with the provision that it could be used with minor revisions. Practically, it gets an average score of 77.64% in the category of higher-order thinking skills, 19 students in the very good category, 7 students in the good category, and 5 students in the moderate category. Thus, The STEM-based mathematics learning module using the PBL model could been said to be well used to improve students’ mathematical understanding and higher-order thinking.